Aradus chinensis spec. nov. - Vásárhelyi, Tamás (Contributions to Entomology = Beiträge zur Entomologie, 1988)
The data of a small palearctic Aradus material deposited in the Department of Taxonomy of Insects in the Eberswalde branch of the Institute of Plant Protection Research (former Deutsches Entomologisches Institut) are published here. Besides the data of 4 species, Aradus chinensis sp. n. is described. The new species belongs to the betulae-group and is more closely related to Aradus hieroglyphicus Sahlberg, 1878. Nomenclatural Acts chinensis Vásárhelyi, 1988 (Aradus), spec. n.